Complex Inferential Processes Are Needed for Implicature Comprehension, but Not for Implicature Production - Mognon, Irene; Sprenger, Simone A.; Kuijper, Sanne J. M.; Hendriks, Petra (Frontiers in Psychology, 2021)
Upon hearing “Some of Michelangelo’s sculptures are in Rome”, adults can easily generate a scalar implicature and infer that the intended meaning of the utterance corresponds to “Some but not all Michelangelo’s sculptures are in Rome”. Comprehension experiments show that preschoolers struggle with this kind of inference until at least five years of age. Surprisingly, the few studies having investigated children’s production of scalar expressions like 'some' and 'all' suggest that production is adult-like already in their third year of life. Thus, children’s production of implicatures seems to develop at least two years before their comprehension of implicatures. In this paper, we present a novel account of scalar implicature generation in the framework of Bidirectional Optimality Theory: the Asymmetry Account. We show that the production-comprehension asymmetry is predicted to emerge because the comprehension of 'some' requires the hearer to consider the speaker’s perspective, but the production of 'some' does not require the speaker to consider the hearer’s perspective. Hence, children’s comprehension of scalar expressions, but not their production of scalar expressions, is predicted to be related to their theory of mind development. Not possessing fully developed theory of mind abilities yet, children thus have difficulty in comprehending scalar expressions such as 'some' in an adult-like way. Our account also explains why variable performance is found in experimental studies testing children’s ability to generate scalar implicatures; moreover, it describes the differences between children’s and adults’ implicature generation in terms of their ability to recursively apply theory of mind; finally, it sheds new light on the question why the interpretation of numerals does not require implicatures generation.